Incidence of Energy Poverty in Nigeria: A Critical Assessment - Obafemi, Frances Ngozi; Ifere, Eugene Okoi (Advances in Social Sciences Research Journal, 2014)
Despite abundant energy sources in Nigeria, three major strategic challenges militate against its efficiency. The aftermath of this inefficiency is health risk, increasing energy prices, low socioeconomic status of the population, increased National debt burden, and rising inflation and massive unemployment. This study is set out to consider an apt remediation for this state of affairs. Using random sampling, households are surveyed in six states of Nigeria and Abuja Federal Capital Territory across the six geopolitical zones. Electricity tariffs, Energy gaps between the high and low income earners, energy spending needs and incomes against a fixed threshold were investigated. A comparison from the income earned shows that above 10 percent of income earned are spent on energy; that both the high and low income earners are energy poor, but the low are more severely hit. The results show that the energy poverty from high energy cost and inefficiency fuels income inequality